2017
DOI: 10.1038/srep40184
|View full text |Cite
|
Sign up to set email alerts
|

In vivo response of AZ31 alloy as biliary stents: a 6 months evaluation in rabbits

Abstract: Mg-based metallic materials have been making continuing progress as vascular stents. However, the research of Mg-based materials as non-vascular stents is still at its primary stage. AZ31 stents hereby were implanted into the common bile duct of rabbits for 6 months. The results revealed an existence of 93.82 ± 1.36% and 30.89 ± 2.46% of the original volume after 1 and 3 month, respectively. Whole blood tests indicated an inflammation decreasing to normal level after 3 month implantation. A benign host respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Similarly, both the serum magnesium and urea nitrogen had an increase during implantation but came back to normal after 6 months. The study concluded the biosafety of Mg alloy AZ31 stent but pointed out the need to improve the corrosion resistance . In another study, Mg and AZ31 craniofacial bone screws were compared by implanting them in the rabbits.…”
Section: Mg and Its Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, both the serum magnesium and urea nitrogen had an increase during implantation but came back to normal after 6 months. The study concluded the biosafety of Mg alloy AZ31 stent but pointed out the need to improve the corrosion resistance . In another study, Mg and AZ31 craniofacial bone screws were compared by implanting them in the rabbits.…”
Section: Mg and Its Alloysmentioning
confidence: 99%
“…There are few studies that discuss the in vivo response of Mg–Al alloys, particularly AZ31 . Liu et al investigated the corrosion and biosafety of AZ31 biliary stents in rabbits.…”
Section: Mg and Its Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also noted in this study that human urine is much more variable in ionic composition between patients than blood or blood plasma [99]. Another application that could be considered is that of a Mg biliary stent, which has recently been investigated in vivo [100]. If future in vitro tests prove necessary for this application, a simulated bile solution would seem appropriate for in vitro biocorrosion testing.…”
Section: Consideration For Other Bodily Fluidsmentioning
confidence: 84%
“…Initial animal experiments have proven that BBS are not only feasible, but also have unique advantages for example, no need for subsequent removal. [10][11][12] Nowadays, a listed product (ELLA-CS, Hradec Kralove, Czech Republic) made from polydioxanone (PDO) has been tested in small-scale clinical trials, showing promising results in treating some simple biliary structures. 13,14 However, PDO has poor mechanical properties, especially much lower Young's modulus than that of other stent materials, 15,16 which can only equip stent with limited radial force and may restrict the widespread application of BBS in treating more complex biliary strictures.…”
Section: Introductionmentioning
confidence: 99%